Efficacy of different probiotic protocols in irritable bowel syndrome: A network meta-analysis - Liang, Ding (Medicine (Baltimore), 2019)
BACKGROUND: Probiotics is a prevalence therapeutic method for irritable bowel syndrome (IBS), but there is lack of comparison in different protocols. We aim to differentiate the reasonable protocols by assessing the efficacy and safety through the combined way of traditional and network meta-analysis. METHOD: PubMed, Medline, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials databases were searched from January 2006 to April 2019. The relative risk (RR) with a 95% confidence interval (CI) was used to combine dichotomous data of responders. RESULT: Among 14 studies included 1695 patients were identified as suitable for inclusion. The proportion of responders was associated with the administration of multispecies probiotics (RR: 1.39; 95% CI: 1.19–1.61) and the dose of 10(9)∼10(10) (RR: 2.08; 95% CI: 1.59–2.71). In network meta-analysis, the protocol of DUO had a significant effect for diarrhea type of IBS compared with placebo (RR: 7.46; 95% CI: 2.00–32.23). In the rest of 4 protocols, no significant difference was found in each other except F19 which appears inferior when compared with Pro (RR: 0.16; 95% CI: 0.03–0.88). Meanwhile, Pro showed a superior effect for undifferentiated-type IBS compared with placebo (RR: 7.16; 95% CI: 1.72–29.89). No probiotics-associated severe adverse event was reported in included studies. CONCLUSION: Probiotics is a safety choice to improve the overall symptoms for IBS patient. The protocols with suitable dose combined of Lactobacillus and Bifidobacterium can have prepotent effects compared with single species or over-dosage protocols. Network meta-analysis shows that DUO may be the first recommendation for diarrhea-type IBS. In the remaining 4 regimes of this study, Pro has a high rank for undifferentiated-type IBS.